Evaluating four –variable screening tool in european population of a sleep clinic for assessing obstructive sleep apnea syndrome - Pataka, Athanasia; Kotoulas, Seraphim; Sourla, Evdokia; Akritidou, Sofia; Panagiotidou, Evangelia; Kalamaras, George; Fekete, Katalin; Argyropoulou, Paraskevi (Asian Journal of Medical Sciences, 2015)
Background: Different questionnaires have been used to evaluate patients with Obstructive sleep apnea/hypopnea syndrome (OSAHS). The 4-Variable screening tool (4-V) was developed and validated in Asian population for identifying moderate to severe OSAHS. Aims and Objectives: To evaluate the ability of 4-V to identify patients at high risk for OSAHS in a European Population visiting a Sleep Clinic. Methods: 1057 (73.8% males), 52±14 years, BMI 33±7kg/m2, Epworth Sleepiness Scale (ESS) 11.5±5.4 and Apnea Hypopnea Index (AHI) 32.7±26.5 were included. All patients had an in laboratory sleep study and 4-V was calculated. Results: The mean 4-V score was 13.3±2.5. Sensitivities of 4-V≥11 for AHI ≥5, ≥15 and ≥30 were 78%, 79% and 81%, respectively; specificities 40.8%, 36%, 32%; positive predictive values (PPV) 84.3%, 71%, 52%; negative predictive values (NPV) 31% , 46.5%, 65% and area under the ROC curve at AHI≥ 15 was 0.58. For 4-V ≥14, sensitivities for AHI ≥5, ≥15 and ≥30 were 50.7%, 55% and 61%, respectively; specificities 78%, 74.4%, 69%; PPV 90.3%, 81%, 64%; NPV 27.9%, 45%, 66% and area under the ROC curve at AHI≥ 15 was 0.68. The 4-V differed significantly between no and mild and between moderate and severe OSAHS, but not between mild and moderate OSAHS in both genders. Sensitivity was better in men, but specificity was higher in women. Conclusion: In Caucasians the 4-V≥14 had low sensitivity and NPV, rather good specificity and PPV. For a cut-off ≥11, sensitivity was better but specificity was low. However the predictive values differed between genders. Asian Journal of Medical Sciences Vol.7(2) 2015 21-27